Paulo Freire and the literacy of young people and adults in the Landless Workers Movement (MST) - Elisiani Vitória Tiepolo (Universidade Federal do Norte do Tocantins, 2019)
This text is part and a survey on the literacy of young people and adults in the Landless Workers Movement (MST). The Movement has as one of its foundations in the pedagogy of Paulo Freire understands literacy beyond the decoding and the mere knowledge of the alphabetical system, but as a process of awareness. In this sense, ownership of the writing is appropriate for an instrument of struggle necessary for the emancipation. However, in your route, the MST has been establishing partnerships that could ensure the implementation of its education projects, and these partnerships also brought into the Movement other theoretical references. More recently, the adoption of the Sim, Eu Posso! (SEP), Cuban method, whose link is with the traditional literacy perspective, has brought a further element of tension and the need to investigate the extent to which Freirean assumptions continue to underpin MST literacy practices. For this investigation, bibliographical research, the analysis of materials produced by the MST and field research.